Employment Law in Context - Cabrelli, David (USA Oxford, 2018)
Employment Law in Context provides students with a complete guide to employment law. David Cabrelli combines extracts from leading cases and articles with insightful and sophisticated author commentary to provide the reader with a full, critical understanding of employment law. As well as providing a thorough grounding in individual labour law, and drawing attention to key and current areas of debate, this title offers the reader detailed analysis of the social, economic, political, and historical context in which employment law operates. An innovative running case study contextualizes employment law and demonstrates its practical applications by following the life-cycle of a company from incorporation, through expansion, to liquidation. Reflection points and examples encourage the development of critical thinking skills and students' ability to view the issues practically.
Age Group: Adult